A Schistosoma mansoni epitope recognized by a protective monoclonal antibody is identical to the stage-specific embryonic antigen 1. - Ko, A I (1990)
In infections with the parasitic trematode Schistosoma mansoni, a component of the host defense is directed against the invading larval form, and carbohydrates on the surface of these larvae are targets for the immune attack during the early stages of infection. To identify such carbohydrate epitopes, which may be suitable for immunization against schistosomiasis, we have previously generated monoclonal antibodies to surface antigens; some of these confer protection to naive mice when passively administered. Here we show that one of the protective antibodies recognizes a determinant present in both the parasite and its mammalian hosts. The immunohistochemical distribution of this determinant in the head of embryonic mice was found to be identical to the stage-specific embryonic antigen 1 (SSEA-1), an epitope abundant in pre-implantation embryos, several adult tissues, and malignant tumors. Oligosaccharides containing the SSEA-1 trisaccharide Gal beta 1-4(Fuc alpha 1-3)GlcNAc inhibit antibody binding to parasite antigen. SSEA-1 antibodies generated from mice immunized with rodent neural antigens bind to the surface of the schistosome larvae and mediate antibody-dependent cellular cytotoxicity. SSEA-1 antibodies are also elicited during human schistosomiasis infection, and this autoantibody response may be involved in the development of the natural immunity against the parasite.